2022
DOI: 10.3390/cancers14071808
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of Diabetes in Cancer Patients Compared to Cancer-Free Population Controls: A Systematic Review and Meta-Analysis

Abstract: Background: Diabetes increases the risk of certain types of cancer. However, the literature regarding the incidence of diabetes after cancer diagnosis is inconsistent. We aimed to assess whether there was a higher incidence of diabetes among cancer patients by performing a systematic review and meta-analysis of results from cohort studies. Methods: A systematic electronic literature search was carried out from cohort studies regarding the incidence of diabetes in cancer patients, using the databases PubMed (ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
4
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
(68 reference statements)
1
10
4
3
Order By: Relevance
“…Contrary to previous studies that reported that the prevalence of DM and the risk of new‐onset DM in cancer survivors increased with cancer stage and cancer treatment, 3,13,42 our study revealed that cancer stage and cancer treatment were not significantly associated with DM prevalence and incidence in LTCS. This discrepancy might be due to the difference in age distribution, cancer types, and follow‐up period between other studies and ours.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous studies that reported that the prevalence of DM and the risk of new‐onset DM in cancer survivors increased with cancer stage and cancer treatment, 3,13,42 our study revealed that cancer stage and cancer treatment were not significantly associated with DM prevalence and incidence in LTCS. This discrepancy might be due to the difference in age distribution, cancer types, and follow‐up period between other studies and ours.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, DM is associated with a higher risk of some cancers such as breast and colorectal cancer 11 . An increased risk of incident DM after cancer diagnosis has also been reported in various studies 12–14 . However, nonsignificant differences between cancer survivors and the cancer‐free population have also been reported 15,16 …”
Section: Introductionmentioning
confidence: 94%
“…A praediabetes és a T2DM, valamint a malignus daganatok közötti összefüggést számos nagy metaanalízis következtetései is megerősítik [1,2,8]. Az IR, az IFG, az IGT és a T2DM fennállása -a teljes népesség körében tapasztalthoz képest -szignifikánsan nagyobb arányban fordul elő számos rákbetegség (például melanoma, NHL, HCC, RCC, CRC, hasnyálmirigy-, húgyhólyag-, prosztata-, emlő-, méhtest-és méhnyakrák stb.)…”
Section: Diabeteshez Társult Tumor Vagy Daganathoz Társult Cukorbeteg...unclassified
“…A szénhidrát-anyagcsere zavarai és a rosszindulatú daganatok közötti összefüggést számos preklinikai és klinikai vizsgálat, valamint nagy metaanalízisek eredményei is alátámasztják [1,2,8]. A kétféle kórállapot közötti szoros kapcsolat okát egyrészt a hasonló anyagcsereváltozások, másrészt a közös molekuláris utak jelentik.…”
Section: Következtetésunclassified
“…Among people aged 65 and older, all cancer incidences have decreased 1.2 per 100,000 people overall in the U.S. from 2014 to 2018 but only decreased 0.6 in Texas [12]. Next, diabetes risk is high among cancer survivors ( [13,14]. While the bene t of glycemic control on cancer outcomes in general has been proved [15], cancer survivors were barely empowered to execute diabetes self-care [16].…”
Section: Introductionmentioning
confidence: 99%